Boshniaks, Muslims or Croats of the Islamic faith? The problem of national identification of Slavic Muslims in Croatia - Kujawa, Karol (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to analyse the processes of national and religious self-identification of Boshniaks/Muslims in Croatia in the years 1990–2006 and to present the policy of the Croatian authorities towards this community. The author uses historical sources, press reports and literature on the subject, employing a historical and political analysis method. Particular attention is paid to the activities of official political parties and Muslim organisations and their role in the process of articulating Muslim identity. The results of the research indicate that the awareness of the distinctiveness of Slavic Muslims in Croatia during the period under study was internally diverse. Some identified themselves as Boshniaks, others as Muslims, and still others adopted the category of ‘Croats of the Islamic faith’. At the same time, a process of intense political and cultural mobilisation of this community towards the concretisation of its own distinctiveness was observed. The main challenges for these activities are the progressive assimilation and attractiveness of Croatian culture, especially for the younger generation.